Ordböckerna och finlandssvenska ords semantik - Nikula, Kristina (Nordiske Studier i Leksikografi, 2003)
It is a well known fact that the use of ännu ‘yet, still’ and redan ‘already’ in the Swedish spoken in Finland somewhat differs from the use in the Swedish spoken in Sweden. This difference has, however, never got any exact semantic description. In this paper it is argued that the difference consists in some small differences concerning some of the presuppositions constituting the meaning of these words.